Comparative Cytotoxic Effects and Possible Mechanisms of Deoxynivalenol, Zearalenone and T-2 Toxin Exposure to Porcine Leydig Cells In Vitro - Lingwei Sun; Jianjun Dai; Jiehuan Xu; Junhua Yang; Defu Zhang (Toxins, 2022)
Mycotoxins such as zearalenone (ZEN), deoxynivalenol (DON) and T-2 toxin (T-2) are the most poisonous biological toxins in food pollution. Mycotoxin contaminations are a global health issue. The aim of the current study was to use porcine Leydig cells as a model to explore the toxic effects and underlying mechanisms of ZEN, DON and T-2. The 50% inhibitory concentration (IC50) of ZEN was 49.71 μM, and the IC50 values of DON and T-2 were 2.49 μM and 97.18 nM, respectively. Based on the values of IC50, ZEN, DON and T-2 exposure resulted in increased cell apoptosis, as well as disrupted mitochondria membrane potential and cell cycle distribution. The results also showed that ZEN and DON significantly reduced testosterone and progesterone secretion in Leydig cells, but T-2 only reduced testosterone secretion. Furthermore, the expression of steroidogenic acute regulatory (StAR) protein and 3β-hydroxysteroid dehydrogenase (3β-HSD) were significantly decreased by ZEN, DON and T-2; whereas the protein expression of cholesterol side-chain cleavage enzyme (CYP11A1) was only significantly decreased by ZEN. Altogether, these data suggest that the ZEN, DON and T-2 toxins resulted in reproductive toxicity involving the inhibition of steroidogenesis and cell proliferation, which contributes to the cellular apoptosis induced by mitochondrial injury in porcine Leydig cells.